Study protocol for a longitudinal study evaluating the impact of rape on women's health and their use of health services in South Africa - Abrahams, N.; Seedat, S.; Lombard, C.; Kengne, A.P.; Myers-Franchi, Bronwyn; Sewnath, A.; Mhlongo, S.; Ramjee, G.; Peer, N.; Garcia-Moreno, C.; Jewkes, R. (BMJ PUBLISHING GROUP, 2017)
Introduction: South Africa is a country known for its high levels of HIV infection and sexual violence. Although the interface between gender-based violence, HIV and mental health has been described, there are substantial gaps in knowledge of the medium-term and long-term health impact. The 2010 Global Burden of Disease study excluded many health outcomes associated with rape and other forms of gender-based violence because systematic reviews revealed huge gaps in data and poor evidence of health effects. This study aims to describe the incidence and attributable burden of physical and mental health problems (including HIV acquisition) in adult women over a 2-year postrape period, through comparison with a cohort of women who have not been raped. The study will substantially advance our understanding of the impact of rape and will generate robust data to assist in the development of postrape health services and the delivery of evidence-based care.